Cement Salvage of Instrumentation-Associated Vertebral Fractures - Xu, R.; O'Connor, K.; Krol, G.; Yamada, Y.; Bilsky, M.; Laufer, I.; Lis, E. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Spinal instrumentation plays a key role in the treatment of spinal instability in patients with metastatic tumors. Poor bone quality, radiation, and diffuse osseous tumor involvement present significant challenges to spinal stabilization with instrumentation and occasionally result in postinstrumentation compression fractures. Vertebral cement augmentation has been effective in the treatment of painful tumor-related compression fractures. Our objective was to describe cement augmentation options in the treatment of vertebral compression fractures associated with spinal instrumentation in patients with metastatic tumors. MATERIALS AND METHODS: Patients who underwent percutaneous vertebral cement augmentation in the treatment of instrumentation-associated vertebral compression fractures between 2005 and 2011 were included in the analysis. Only fractures that occurred within the construct or at an adjacent level were included. The change in Visual Analog Scale and need for further surgery were analyzed. RESULTS: Eleven patients met the inclusion criteria, with 8 tumors located in the thoracic spine and 3 tumors in the lumbar spine. The median time between instrumented surgery and vertebral augmentation was 5 months (1–48 months) and the median follow-up after cement augmentation was 24 months (4–59 months). A total of 22 vertebrae that were either within or immediately adjacent to the surgical instrumentation underwent vertebral augmentation. All patients reported a decrease in their pain scores (mean decrease: 6 Visual Analog Scale points; P < .003). One patient required reoperation after cement augmentation. None of the patients experienced vertebral cement augmentation–related complications. CONCLUSIONS: Vertebral cement augmentation represents a safe and effective treatment option in patients with recurrent or progressive back pain and instrumentation-associated vertebral compression fractures. VASVisual Analog ScaleSRSstereotactic radiosurgery